An analysis of research productivity in Saudi Arabia and Iran - Mushtaq Ahmed, Younus Ahmed; Mohamad Diah, Nurazzura (The Informing Science Institute (ISI), 2019)
Aim/Purpose Education is vital as it is a major investment in human capital. Tertiary education, in particular, contributes to the growth of knowledge and advances skills, which helps in the development of a country. This paper aims to look at the research and technological output at the tertiary level in Saudi Arabia and Iran.